(3edhc GdcdGes - (3eMeO Hf YHO GdhgGH Hf OGhO GdgeOGfj GdcGXej EeGe GdMQejf,J (B1305 (3g` s
(3ChdgG (B:s
(3HGdcSQ hGdeYdd dCf ef Mbg GdJYdjd Ydjg s
(3BNQgG (B:s
(3hHYOgG Cf de JJYbH HGdJhHI hGdfOH jcJHhf hdjcf gPG BNQ Gdbhd ai GdeLdO GdChd ef cJGHfG GdehShe Hedhc GdcdGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(1742/1) s
Keywords: (3GdeYGQa GdYGeIs